2014
DOI: 10.1128/jvi.01447-14
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Study of the Interaction between Human Herpesvirus 6B Glycoprotein Complex and Its Cellular Receptor, Human CD134

Abstract: Recently, we identified a novel receptor, CD134, which interacts with the human herpesvirus 6B (HHV-6B) glycoprotein (g)H/ gL/gQ1/gQ2 complex and plays a key role in the entry of HHV-6B into target cells. However, details of the interaction between the HHV-6B gH/gL/gQ1/gQ2 complex and CD134 were unknown. In this study, we identified a cysteine-rich domain (CRD), CDR2, of CD134 that is critical for binding to the HHV-6B glycoprotein complex and HHV-6B infection. Furthermore, we found that the expression of HHV-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…In this study, we showed that the neutralizing activity of OHV-3 is weaker than that of KH-1. The reason would be that KH-1 recognizes gQ1, and gQ1 is directly responsible for CD134 binding (25).The direct binding of KH-1 to gQ1 of the gH/gL/gQ1/gQ2 complex could disturb the interaction of gQ1 with CD134, because the tetrameric complex with a gQ1 mutant that was not recognized by KH-1 could not bind to CD134 (18,25) (Fig. 7A).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we showed that the neutralizing activity of OHV-3 is weaker than that of KH-1. The reason would be that KH-1 recognizes gQ1, and gQ1 is directly responsible for CD134 binding (25).The direct binding of KH-1 to gQ1 of the gH/gL/gQ1/gQ2 complex could disturb the interaction of gQ1 with CD134, because the tetrameric complex with a gQ1 mutant that was not recognized by KH-1 could not bind to CD134 (18,25) (Fig. 7A).…”
Section: Discussionmentioning
confidence: 99%
“…IE1A and IE1B are large (150 kDa) proteins involved in preventing type I Interferon synthesis and signaling (26, 27). Glycoproteins Q (Q1 and Q2) are part of a multiprotein assembly responsible for receptor binding and viral entry (28, 29). iciHHV-6A expression was noticeably higher in the brain in both the GTEx and MSBB datasets compared to iciHHV-6B (Figures 2 and 3).…”
Section: Resultsmentioning
confidence: 99%
“…We replaced these two residues with the homologous residues in mCD134 (K79D and R95L) and then examined the interaction between the CD134 mutants and the HHV-6B gH/gL/gQ1/gQ2 complex by immunoprecipitation with an anti-gH antibody followed by Western blotting (in our previous study, we confirmed that both immunoprecipitation and pulldown assays could be used for the analysis of the HHV-6 receptor-ligand interaction [10,11]). The interaction between the HHV-6B complex and hCD134 was detected when R95, but not K79, was mutated.…”
mentioning
confidence: 88%
“…The HHV-6A ligand, glycoprotein H (gH)/gL/gQ1/gQ2 complex, binds to human CD46, a ubiquitously expressed molecule that may contribute to the relatively broad cell tropism of HHV-6A (6)(7)(8). In contrast, human CD134 (hCD134) is the specific receptor for HHV-6B (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation